1999
DOI: 10.1097/00004424-199905000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aging on Gastrointestinal Transit Time

Abstract: Delayed gastric emptying of solid foods could result from progressive autonomic nerve dysfunction occurring with aging. The stomach does not seem to be the segment of the digestive tract that is primarily responsible for the alteration of total GI time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 11 publications
2
31
1
5
Order By: Relevance
“…In the fasted state, gastric motility occurs in continuity with the rest of the intestine as part of the migrating motor complex (MMC) 1. In the fed state, gastric motility is highly dependent on meal composition 1, and may be slowed by diseases such as diabetes 2, in people with high body mass index (BMI) 3 and in the elderly 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fasted state, gastric motility occurs in continuity with the rest of the intestine as part of the migrating motor complex (MMC) 1. In the fed state, gastric motility is highly dependent on meal composition 1, and may be slowed by diseases such as diabetes 2, in people with high body mass index (BMI) 3 and in the elderly 4.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric emptying profiles are often noted to be biphasic, especially after a solid and/or high‐fat meal, due to inhibitory feedback from the small intestine 1. The first phase is indicated either by a lag time 10, 11, 12 or an initial faster process 4, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Com o avançar da idade, ocorre diminuição na motilidade esofágica e colônica (BUTT et al, 1993;HOLLINS;CASTELL, 1974;KHAN et al, 1977;WADE;EVANS;LIEB, 2002), comprometimento do esvaziamento gástrico (BROGNA et al, 1999;HOROWITZ et al, 1984;SMITS;LEFEBVRE, 1996) e aumento no trânsito intestinal (ANU-RAS; LEONING-BAUCKE, 1984;WADE;EVANS;LIEB, 2002). A alteração do número de neurônios mioentéricos é um dos fatores que contribuem para o comprometimento da motilidade do tubo digestório ao longo do envelhecimento (DE SOUZA et al, 1993;EL-SALHY;SABDSTRÖM;HOLMLUND, 1999;GABELLA, 1989;GOMES;DE SOU-ZA;LIBERTI, 1997;POWLEY, 2001POWLEY, , 2007SANTER;BAKER, 1988).…”
Section: Introductionunclassified
“…Some authors reported that in the aging process many changes can occur in the digestive system, such as, decreasing of esophagus motility (Butt et al 1993) and consequently decreasing of bacterial colonies (Madsen 1992), delayed gastric depletion (Brogna et al 1999) and increasing of intestinal transit (Anuras and Leoning-baucke 1984). During the entire process of aging can be observed from changes lighter in the gastrointestinal tract, such as constipation, even more serious conditions such as intestinal obstruction (Shamburek and Farrar 1990).…”
Section: Introductionmentioning
confidence: 99%